2019
DOI: 10.3233/kca-180043
|View full text |Cite
|
Sign up to set email alerts
|

The ‘Achilles Heel’ of Metabolism in Renal Cell Carcinoma: Glutaminase Inhibition as a Rational Treatment Strategy

Abstract: An important hallmark of cancer is ‘metabolic reprogramming’ or the rewiring of cellular metabolism to support rapid cell proliferation [ 1–5 ]. Metabolic reprogramming through oncometabolite-mediated transformation or activation of oncogenes in renal cell carcinoma (RCC) globally impacts energy production as well as glucose and glutamine utilization in RCC cells, which can promote dependence on glutamine supply to support cell growth and proliferation [ 6, 7 ]. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 184 publications
1
50
0
Order By: Relevance
“…We also found argininosuccinate synthase 1 (ASS1) expression was downregulated, which can increase aspartate availability and is associated with poor prognosis in multiple cancers 34,35 . In RCC, an increase in aspartate levels can promote cell proliferation due to its role in nucleotide synthesis 36 . In KICH, genes related to the aspartate-malate shuttle were also upregulated suggesting that aspartate can act as an anaplerotic source for the TCA cycle.…”
Section: Discussionmentioning
confidence: 99%
“…We also found argininosuccinate synthase 1 (ASS1) expression was downregulated, which can increase aspartate availability and is associated with poor prognosis in multiple cancers 34,35 . In RCC, an increase in aspartate levels can promote cell proliferation due to its role in nucleotide synthesis 36 . In KICH, genes related to the aspartate-malate shuttle were also upregulated suggesting that aspartate can act as an anaplerotic source for the TCA cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some tumour cells in vitro are unable to survive in the absence of an exogenous supply of glutamine . Consequently, cells develop a metabolic strategy to provide a source of carbon other than glucose to derive the carbon that is necessary to fuel the tricarboxylic acid (TCA) cycle . Recently, it has been shown that glutamine can enhance cancer progression independently of its metabolic role, as it can act as a signalling agent to activate the transcription factor STAT3, which is required to mediate the proliferative effects of glutamine on cancer cells .…”
Section: Glutamine Metabolism and Addiction In Cancermentioning
confidence: 99%
“…8,10 Consequently, cells develop a metabolic strategy to provide a source of carbon other than glucose to derive the carbon that is necessary to fuel the tricarboxylic acid (TCA) cycle. 11 Recently, it has been shown that glutamine can enhance cancer progression independently of its metabolic role, as it can act as a signalling agent to activate the transcription factor STAT3, which is required to mediate the proliferative effects of glutamine on cancer cells. 12 Furthermore, glutamine can indirectly activate other signalling pathways, such as the mammalian target of rapamycin complex 1 (mTORC1) pathway; mTORC1 is a critical kinase that regulates cell growth and proliferation, as glutamine-derived a-KG is required for GTP loading of RagB and subsequent activation of mTORC1.…”
Section: Glutamine Metabolism and Addiction In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, GLS2 is a druggable metabolic node for breast cancer. In RCC, metabolic reprogramming is closely associated with disease progression and metastasis; as a result, glutaminase inhibitors are a novel strategy for RCC treatment [32]. Although GLS2 is predominantly found in liver tissue, its function as a tumor suppressor in RCC requires further discussion.…”
Section: Discussionmentioning
confidence: 99%